2012
DOI: 10.1139/y2012-091
|View full text |Cite
|
Sign up to set email alerts
|

d-Propranolol protects against oxidative stress and progressive cardiac dysfunction in iron overloaded rats

Abstract: d-Propranolol (d-Pro: 2–8 mg·(kg body mass)−1·day−1) protected against cardiac dysfunction and oxidative stress during 3–5 weeks of iron overload (2 mg Fe–dextran·(g body mass)−1·week−1) in Sprague–Dawley rats. At 3 weeks, hearts were perfused in working mode to obtain baseline function; red blood cell glutathione, plasma 8-isoprostane, neutrophil basal superoxide production, lysosomal-derived plasma N-acetyl-β-galactosaminidase (NAGA) activity, ventricular iron content, and cardiac iron deposition were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…20, 21 The anti-inflammatory properties of Prop have been well-documented; its use has been associated with decreased edema in mesenchymal stromal cells with traumatic brain injury 22 as well as decreased cardiac inflammation and oxidative stress markers such as glutathione and isoprostanes. 23 Prop attenuates inflammatory cell infiltration, expression of the cytokines TNF-α and IL-8, 24 and airway inflammation 25 in a rat model of cigarette smoke exposure. The combined administration of Ox and Prop may stimulate protein synthesis and anabolism owing to Ox and decrease the inflammatory cascade owing to Prop, resulting in an additive effect that increases growth of pediatric burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…20, 21 The anti-inflammatory properties of Prop have been well-documented; its use has been associated with decreased edema in mesenchymal stromal cells with traumatic brain injury 22 as well as decreased cardiac inflammation and oxidative stress markers such as glutathione and isoprostanes. 23 Prop attenuates inflammatory cell infiltration, expression of the cytokines TNF-α and IL-8, 24 and airway inflammation 25 in a rat model of cigarette smoke exposure. The combined administration of Ox and Prop may stimulate protein synthesis and anabolism owing to Ox and decrease the inflammatory cascade owing to Prop, resulting in an additive effect that increases growth of pediatric burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that 8-isoprostane is a prostaglandin (PG)-F 2 -like compound belonging to the F 2 isoprostane class which is produced by the free radical-catalyzed peroxidation of arachidonic acid [ 65 , 66 ]. 8-isoprostane is an accurate marker of lipid peroxidation and has been used to determine oxidative stress in in vivo [ 66 , 67 ], especially in iron-overloaded rat model [ 68 ], which could be more specific to oxidative stress than MDA.…”
Section: Limitationsmentioning
confidence: 99%
“…A 15 MHz probe was used to image hearts. Echocardiography was performed on anesthetized mice (2% isoflurane with 100% O 2 ; E-Z Anesthesia Chamber with nose cone, Euthanex Co., Palmer, PA, USA), and heart rate and rectal temperature were monitored [12,14]. Mice were placed on a heated platform with paws taped to electrode pads for monitoring [14].…”
Section: Non-invasive Echocardiographymentioning
confidence: 99%
“…Thus, overproduction of superoxide at a time of excessive iron (overload), may have a deleterious systemic and organ specific injurious impact. We have previously shown that treatment with select antioxidants provided significant cardiovascular functional protection to rodents exposed to chronic iron overload [12]. However, it is unclear whether the oxidative stress resulting from NADPH oxidase activity is a major contributor to the cardiac dysfunction observed during iron overload.…”
Section: Introductionmentioning
confidence: 99%